Two-year interim safety results of the 0.2 µg/day fluocinolone acetonide intravitreal implant for the treatment of diabetic macular oedema: the observational PALADIN study. Issue 3 (27th May 2020) - Mansour, Sam E; Kiernan, Daniel F; Roth, Daniel B; Eichenbaum, David; Holekamp, Nancy M; Kaba, Samer; Werts, Erica
Abstract : Background: The 0.2 µg/day fluocinolone acetonide (FAc) implant delivers continuous, low-dose, intravitreal corticosteroid for the treatment of diabetic macular oedema (DMO). This ongoing, 3-year, observational clinical trial provides long-term, 'real-world' safety results for the FAc implant in DMO. Methods: This 24-month interim analysis of a prospective, observational study investigated patients with DMO receiving the commercially available intravitreal 0.2 µg/day FAc implant. The primary outcome was incidence of intraocular pressure (IOP)-lowering procedures. Other IOP-related signals and their relationship to previous corticosteroid exposure, best-corrected visual acuity, central subfield thickness (CST), ocular adverse events and frequency of other treatments were also measured. Results: Data were collected from 95 previously steroid-challenged patients (115 study eyes) for up to 36 months pre-FAc and 24 months post-FAc implant. Mean IOP for the overall population remained stable post-FAc compared with pre-FAc implant. IOP-related procedures remained infrequent (two IOP-lowering surgeries pre-FAc; two trabeculoplasties and four IOP-lowering surgeries post-FAc). Mean visual acuity was stable post-FAc (mean improvement of 1–3 letters) and fewer DMO treatments were required per year following FAc implant. Mean CST was significantly reduced at 24 months post-FAc implant (p<0.001) and the percentage of patients with CST ≤300 µm was significantly increased (p=0.041). Conclusion: Few IOP-related procedures were reported during the 24 months post-FAc implant. Positive efficacy outcomes were noted after treatment, with stabilisation of vision and reduction in inflammation, demonstrated by CST. The FAc implant has a favourable benefit–risk profile in the management of DMO, especially when administered after a prior steroid challenge. Trial registration number: NCT02424019 .